The Nashville sound [compact disc] - Isbell, Jason (Southeastern Records, 2017)
Jason Isbell is back with the follow-up to his two-time Grammy Award-winning album Something More Than Free. The first single from his new album, Hope the High Road, made its debut on Entertainment Weekly's website.